Pengaruh Konten Instagram @interstudiofficial dan Opini Mahasiswa terhadap Citra Perguruan Tinggi InterStudi - Isfa Kaharmudzakir; Mohamad Ichlas El Qudsi (Jurnal Riset Komunikasi, 2022)
The interest of Instagram users to find out information from another party's Instagram account is the unique and interesting content contained in it. When content is considered useful, followers will provide positive comments and opinions. This study aims to determine the extent to which Instagram content uploaded to the @interstudiofficial account and student opinions affect the image of InterStudi colleges. This research method uses an explanatory quantitative approach, which was carried out on 97 respondents who are followers of the @interstudiofficial Instagram account. This study wants to explain the relationship between the three variables. Data were analyzed using multiple linear regression. The results show that Instagram content and student opinions have an effect on the image of the InterStudi college. These findings explain that the Instagram account uploaded by the @interstudiofficial account must have a positive value so that followers will provide comments and opinions which ultimately have a good effect on InterStudi's image.